Stalking the True Self Through the Jungles of Authenticity: Problems, Contradictions, Inconsistencies, Disturbing Findings—and a Possible Way Forward. Issue 1 (March 2019) - Baumeister, Roy F.
Research on authenticity frequently invokes notions of true self, but is there such thing? The question must be answered twice, given frequent confusion and conflation of self with self-concept. Summarizing and integrating themes from authenticity research as evident in this special issue, I draw these conclusions. True self-concepts are more plausible than genuinely true selves, if the latter are independent entities distinct from actual behavior and experience. Yet rather than a single true self-concept, people have multiple nonfalse ones, none of which is entirely true. Among these, the pragmatically most important is the desired reputation, given the social-cultural orientation of humankind. Desired reputation is more a guide and goal than a reality, but successes and failures at achieving that reputation will produce welcome and unwelcome feelings that are likely reported as feeling authentic and inauthentic (respectively). Understanding authenticity in this way solves some of the perennial problems that beset research and theory on authenticity, especially positive distortion and external rather than internal orientation.